Evaluation of differences between Chiralpak IA and Chiralpak AD-RH amylose-based chiral stationary phases in reversed-phase high-performance liquid chromatography - Kalíková, Květa; Geryk, Radim; Vozka, Jiří; Tesařová, Eva (Journal of separation science, 2015)
Polysaccharide-based chiral stationary phases can be used for the enantioselective separation of a wide range of structurally different compounds. These phases are available with chiral selectors coated or immobilized on silica gel support. The means of attachment of the chiral selector to the carrier can influence the separation performance of these stationary phases. This paper deals with evaluation of differences in the separation abilities of coated Chiralpak AD-RH versus immobilized Chiralpak IA amylose-based stationary phases in the reversed-phase mode of high-performance liquid chromatography. A set of chiral analytes was separated under acidic and basic conditions. Differences were observed in the enantioseparation potential of the tested phases. The linear-free energy relationship and additional evaluation of ionic interactions were used to ascertain whether the interactions that participate in retention and enantioseparation are affected by the means of preparation of these phases. All the interactions covered by the linear-free energy relationship were significant for the studied phases and their absolute values were almost always higher for the coated phase. Ionic interactions were found to be more important on the immobilized stationary phase but did not contribute to any improvement in the enantioselective separation performance.
Keywords: Interaction mechanisms; Enantioselective separations; Amylose; Chiral stationary phases